AGAMA SEBAGAI “KOMODITAS”? Memosisikan Majelis Shalawat sebagai Waralaba Religius - Anggrisia, Nur Fitria (Universitas Nurul Jadid, 2020)
This study attempts to analyze the ways shalawatan which is originally held for spiritual consumption needs (functional) become a commodity with an exchange rate (economical). Based on qualitative research on the Majelis Shalawat Syubbanul Muslimin Probolinggo by using Mosco's analysis method of media commodification, this study resulted that in the performance of Majelis Shalawat Syubbanul Muslimin in Kalikajar Probolinggo, in addition to the role of charismatic and motivational figures in the fulfillment of needs, the process of religious commodification is also obtained in each shalawat performance through audiences’ (Nahdliyin) relation to artists (Gus Hafidz) who basically have similarities with franchise models, such as Alfamart or Indomaret.